Growth mindset and innovative ideas: The critical role of beliefs about intelligence among higher education students - Amien, Moh. Sulthon; Hidayatullah, Achmad; Deviyanti, Rafista; Lestari, Sri (Universitas Negeri Yogyakarta, 2025)
The purpose of this study is to explore the levels of innovative thinking, growth, and a fixed mindset among higher education students in Indonesia. This study also examined the association between mindset and innovative ideas. This cross-sectional study involved 294 students from 2 higher education institutions. Descriptive statistics, t-test, and regression analysis were employed to analyse the data. The results of this study suggest that most students tend to generate new ideas frequently. Students in the health program have lower growth beliefs, growth practices, and effort, and firmer fixed beliefs than students in another program. A growth mindset significantly predicts the generation of innovative ideas. This study contributes to the literature review and teaching practice.